Targeted activation of melanoma differentiation-associated protein 5 (MDA5) for immunotherapy of pancreatic carcinoma - Duewell, Peter (Oncoimmunology, 2015)
The RIG-I-like helicase melanoma differentiation-associated protein 5 (MDA5) is an innate immune receptor for double-stranded viral RNA (dsRNA) that, upon activation, induces a Type I interferon (IFN)-driven immune response. In the present study, we demonstrate that human und murine pancreatic cancer cells express functional MDA5 and are highly sensitive to MDA5-induced cell death. Activation of MDA5 by cytosolic delivery of the synthetic dsRNA analog poly(I:C) led to phosphorylation of the transcription factor IRF3, IFNβ production and upregulation of MHC-I expression. MDA5 signaling also induced tumor cell apoptosis via the intrinsic pathway and sensitized tumor cells toward extrinsic, Fas-mediated apoptosis. Systemic treatment of orthotopic pancreatic cancer-bearing mice with the MDA5 ligand resulted in activated CD8(+) T cell tumor infiltration, an increased frequency of tumor antigen-specific CD8(+) T cells and an immunogenic cytokine milieu in the tumor microenvironment. These effects were paralleled by MDA5-induced pronounced tumor cell death in situ and significantly prolonged survival in two different mouse models for pancreatic cancer, an immunotherapeutic response dependent on CD8(+) T cells. Treated mice were further protected from subsequent tumor challenge. In summary, we identified MDA5 as a novel therapeutic target for overcoming apoptosis resistance and tumor-mediated immunosuppression in pancreatic cancer. MDA5 ligands link innate with adaptive immune mechanisms for effective tumor control.